Study of thermo-regulation as a worsening marker of experimental sepsis in an animal model - André Luiz Thomaz de Souza; Marcelo Eduardo Batalhão; Evelin Capellari Cárnio (Universidade de São Paulo, 2020)
Objective: to analyze variations in body temperature and in plasma nitrate and lactate concentrations in rats submitted to the experimental sepsis model. Method: a total of 40 rats divided equally into five groups. The induction of endotoxemia was performed with intravenous administration of lipopolysaccharide, 0.5 mg/Kg, 1.5 mg/Kg, 3.0 mg/Kg, and 10 mg/Kg, respectively. The control group received 0.5 mL of saline solution. The experiment lasted six hours, with evaluations performed at 0 (baseline data), 2nd, 4th, and 6thhours. Results: The animals that received doses up to 3.0 mg/kg showed a significant increase in body temperature compared to the group with 10 mg/kg, which showed a decrease in these values. The increase in plasma nitrate and lactate concentrations in the groups with lipopolysaccharide was significantly higher than in the group that received the saline solution and was correlated with the increase in body temperature. Conclusion: the variations in body temperature observed in this study showed the dose-dependent effect of lipopolysaccharide and were correlated with the increase in the concentrations of nitrate and plasma lactate biomarkers. The implications of this study are the importance of monitoring body temperature, together with the assessment of these pathophysiological markers, which suggest worsening in the prognosis of sepsis.